Terapi Ice Cube’s Terhadap Penurunan Intensitas Rasa Haus Pada Pasien Gagal Ginjal Menjalani Hemodialisa - Apriyani; Zulaika; Dela Putri Asmarita (Jurnal Keperawatan Malang, 2025)
Background: CKD disease is permanent and cannot be cured. This condition requires long-term treatment, such as peritoneal dialysis, kidney transplantation, hemodialysis, and outpatient care. Hemodialysis has a very important role in balancing fluids in the body, helping in the management of kidney disease, and increasing the patient's quality of life. Thirst is very important to be reduced as an effort to intervene in CKD patients. One of the interventions used is ice cube therapy. Purpose: the influence of ice cube therapy on reducing the intensity of fluid intake in chronic kidney failure patients undergoing hemodialysis is known. Methods: This quantitative pre-experimental study uses a one-group pretest-posttest design. This research used purposive methods. With 30 responders. Patients were given 10 cc ice cubes to suck for 5 minutes as therapy. VAS was utilized for measuring. Wilcoxon statistical analysis was used. Result: Ice cube treatment reduced fluid consumption in renal failure patients on hemodialysis with a mean thirst level of 3.53 before the intervention and 3.10 afterward. The p-value was 0.000. Implication: The study found that ice cube therapy reduced thirst in hemodialysis patients with kidney failure. The patient's thirst should be stabilized with this finding. Furthermore, researchers are expected to add variables and control groups in subsequent studies.